HR Management Strategies In Improving Organizational Performance In The Era Of Digital Disruption: An Analysis Of The Role Of Transformational Leadership And Employee Engagement - Nurhasanah Pasaribu; Paul Sopacua; Suhardy; Nurul Hudaini; Dorthy Ellayany Sinaga; Rasyid Tarmizi; Rizal Ula Ananta Fauzi; Diah Fatma Sjoraida, (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
The era of digital disruption has brought significant changes in the business landscape and demanded organizations to adapt more dynamic and innovative human resource (HR) management strategies. This study aims to analyze HR management strategies in improving organizational performance by emphasizing transformational leadership roles and employee engagement. The research method used is a quantitative approach by collecting data through surveys of employees from various industrial sectors that are undergoing digital transformation. The results of the analysis show that transformational leadership has a significant influence on increasing employee engagement, which ultimately positively impacts the overall performance of the organization. This study confirms the importance of integration between adaptive HR management strategies, visionary leadership, and high employee engagement in the face of digital challenges. These findings provide practical implications for organizational leaders to develop a responsive, collaborative, and innovation-based work culture to achieve sustainable competitive advantage.